2016
DOI: 10.1007/s11064-016-2119-2
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated TLR3 Promotes Neuropathic Pain by Regulating Autophagy in Rat With L5 Spinal Nerve Ligation Model

Abstract: Microglia, rapidly activated following peripheral nerve injury (PNI), accumulate within the spinal cord and adopt inflammation that contributes to development and maintenance of neuropathic pain. Microglia express functional Toll-like receptors (TLRs), which play pivotal roles in regulating inflammatory processes. However, little is known about the role of TLR3 in regulating neuropathic pain after PNI. Here TLR3 expression and autophagy activation was assayed in dorsal root ganglions and in microglia following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 41 publications
0
28
0
Order By: Relevance
“…Patients with diabetes, cancer, and AIDS also experience with neuropathic pain. Several lines of evidence indicate that expression changes of mRNA and protein in the DRG are related to neuropathic pain [5, 33]. It is well known that miRNAs are involved in the regulation of neuropathic pain [1, 3].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with diabetes, cancer, and AIDS also experience with neuropathic pain. Several lines of evidence indicate that expression changes of mRNA and protein in the DRG are related to neuropathic pain [5, 33]. It is well known that miRNAs are involved in the regulation of neuropathic pain [1, 3].…”
Section: Discussionmentioning
confidence: 99%
“…GO enrichment analysis revealed that thousands of target genes were involved in the GO term: biological processes, cellular component, and molecular function, which indicates that these differential circRNAs may influence genes of varied biological function. KEGG analysis showed that there were 112 pathways related to the 100 circRNAs, the top three were reported to be related to neuropathic pain: the Hippo signaling pathway,40 MAPK signaling pathway,4143 and endocytosis 44,45…”
Section: Discussionmentioning
confidence: 99%
“…Beyond the previous observations in cultured DRGs, there are few investigations into the relationship between TLR3 and pain. A recent investigation identified elevated TLR3 mRNA and protein in the rat spinal cord following nerve injury, along with increased activation of microglial autophagy in response to nerve injury or application of TLR3 agonists (Chen & Lu, 2017). In a separate model of chronic pancreatitis, intrathecal infusion of TLR3 antisense oligodeoxynucleotide to knockdown TLR3 expression resulted in modest relief from mechanical allodynia (Qian, et al, 2011), suggesting TLR3 mechanisms participate under certain conditions of inflammatory pain.…”
Section: Tlr3 Tlr7 Tlr9: Emerging Roles Of Endosomal Tlrs and Pementioning
confidence: 99%